2014
DOI: 10.1021/ct500507f
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Cost-Effective Approach to the Calculation of Kinetic and Thermodynamic Properties of Methyl Methacrylate Homopolymerization: A Comprehensive Theoretical Study

Abstract: In this work, we carried out a comprehensive density functional theory (DFT) study on the basis of a trimer-to-tetramer radical reaction model to assess a cost-effective approach to perform the calculation of kinetic and thermodynamic properties of methyl methacrylate (MMA) free-radical homopolymerization. By comparing results from several different functionals (PBE, M06-2X, wB97XD, KMLYP, and MPW1B95), in conjunction with a series of basis sets (6-31G(d,p), 6-31+G(d,p), 6-31G(2df,p), 6-311G(d,p), 6-311+G(d,p)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…6, they can be arranged in an scis and s-trans conformation. Different authors [22][23][24] have studied the conformers of model monomers and their ndings suggest that all acrylic monomers, except MMA, are more stable in their cis conformation. For the particular case of the MMA monomer, long-range stabilizing interactions have been proposed as the origin of its preferential trans-conformation.…”
Section: Geometrical Features Of Model Vinyl Compounds and Asymmetricmentioning
confidence: 99%
“…6, they can be arranged in an scis and s-trans conformation. Different authors [22][23][24] have studied the conformers of model monomers and their ndings suggest that all acrylic monomers, except MMA, are more stable in their cis conformation. For the particular case of the MMA monomer, long-range stabilizing interactions have been proposed as the origin of its preferential trans-conformation.…”
Section: Geometrical Features Of Model Vinyl Compounds and Asymmetricmentioning
confidence: 99%
“…Consistent with our previous work on MMA homopropagation, we explored all possible conformers of reactants and TS originated from the s‐cis and s‐trans isomerization of a methacrylate monomer . In addition, we found that for ECPMA–MMA crosspropagation, another conformational consideration became important for the TS, which is the type of rotamer of the CC bond forming region, namely, anti and gauche, as depicted in Figure .…”
Section: Resultsmentioning
confidence: 56%
“…In the precedent work, we established a cost‐effective computational approach to calculate kinetic parameters describing MMA homopropagation . The predicted activation energy was in good agreement with the experimentally determined value.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations